Permanent Sovereignty in the Context of Trade Law: Addressing Legal Constraints on Downstream Policy Implementation - Gea, Gita Venolita Valentina; Fabio, Matthew; Jaqline, Djayakusli (Hang Tuah Law Journal, 2025)
The Government of Indonesia has expressed a strong commitment to enhancing national welfare through the implementation of downstream policies across various trade sectors, including those involving natural resource commodities. A range of regulatory measures has been introduced, from mandates on domestic processing to the imposition of export bans. Nevertheless, the execution of such downstream policies has raised concerns regarding their compatibility with obligations under international trade agreements to which Indonesia is a party. This paper seeks to analyze the implementation of downstream policies in light of international trade law. Employing a normative juridical approach, the study finds that down streaming in the natural resources sector constitutes a manifestation of the principle of permanent sovereignty over natural resources. A thorough legal examination of this principle suggests that it may qualify as a norm of jus cogens, thereby holding a superior normative status that can prevail over conflicting provisions in international trade agreements.